If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3xy + -5a = 4c Reorder the terms: -5a + 3xy = 4c Solving -5a + 3xy = 4c Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3xy' to each side of the equation. -5a + 3xy + -3xy = 4c + -3xy Combine like terms: 3xy + -3xy = 0 -5a + 0 = 4c + -3xy -5a = 4c + -3xy Divide each side by '-5'. a = -0.8c + 0.6xy Simplifying a = -0.8c + 0.6xy
| 3n-18/5=5/7 | | -5=3+2y | | -y+276=32 | | 12(-12)= | | 6-12=z/-8 | | 0=(2x^3)-8x-2x^3 | | 17+d=-7d-7 | | 7x+51=2x-13 | | 25+6w=11w | | 11=5.5x+258 | | 4-3[x+2]-2[x-4]+8=1 | | w=24-2w | | n/9=20 | | (2^2x^2/xy^3)^2 | | 2+20x=19x-11 | | 95=.05s^2+1.1s | | -11(3/2) | | 4v+24=10v | | 52+2x=90 | | y=258+60.5x | | 5x/-11=-54 | | x^2+6x+13-12y=0 | | 10p+5= | | y=5.5x(11)+258 | | Y/7=11/8 | | x+97=x+32 | | 3[x+2]+4=31 | | b+9=12.2 | | 38=b-47 | | -2n-1=-7 | | 3v/2=15 | | -v/7=53 |